Discussion of the Economic Effects of Involuntary Uniformity in the Financial Reporting of R&D Expenditures and Accounting for Research and Development Costs: The Impact on Research and Development Expenditures - Marshall, William (Journal of Accounting Research, 1980)
William Marshall, Discussion of the Economic Effects of Involuntary Uniformity in the Financial Reporting of R&D Expenditures and Accounting for Research and Development Costs: The Impact on Research and Development Expenditures, Journal of Accounting Research, Vol. 18, Studies on Economic Consequences of Financial and Managerial Accounting: Effects on Corporate Incentives and Decisions (1980), pp. 84-90